Influence of Perceived Organizational Support on Organizational Commitment and Turnover Intention through the Mediating Role of Happiness at Work - Kurniawan, Hafiludin (Jurnal Multidisiplin Madani, 2024)
The high intention to switch jobs can have a negative impact on the company, especially experienced by generations with less commitment to long-term employment, posing challenges in human resource management. The research aims to understand and analyze the influence of Perceived Organizational Support on Organizational Commitment and Turnover Intention through Happiness at Work. This quantitative study involved 223 employee respondents at PT. Permodalan Nasional Madani Area Demak. Data analysis was conducted using SEM-PLS. The results indicate that Perceived Organizational Support positively influences Organizational Commitment, positively influences Happiness At Work, and negatively influences Turnover Intention. Organizational Commitment positively influences Happiness at Work, and both negatively influence Turnover Intention. Happiness At Work negatively influences Turnover Intention. Additionally, Perceived Organizational Support has an influence on Organizational Commitment and Turnover Intention through the mediating factor of Happiness at Work